2023
DOI: 10.1136/bmjopen-2022-068645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of locomotive syndrome categorised by the 25-question Geriatric Locomotive Function Scale: a systematic review

Abstract: ObjectivesThe purpose of this study was to compile the currently available evidence on the clinical characteristics of the locomotive syndrome (LS) categorised by the 25-question Geriatric Locomotive Function Scale (GLFS-25) and clarify its clinical usefulness for assessing mobility function.DesignSystematic review.Data sourcesThe PubMed and Google Scholar were searched for the relevant studies on 20 March 2022.Eligibility criteriaWe included relevant peer-reviewed articles, available in English language, on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“… 8 Furthermore, LS diagnosed using the GLFS-25 was associated with a lower maximum stride, slower usual gait speed, and longer timed up-and-go time; thus, the GLFS-25 is useful for assessing clinical mobility function. 17 Japanese population-based cohort studies of elderly individuals demonstrated that increased M-PA and V-PA, and decreased sedentary time measured using self-reported questionnaires were associated with a lower risk of functional disability requiring nursing care. 40 Therefore, our findings regarding the relationship between sedentary behavior and LS, defined by the GLFS-25, align with prior research exploring the relationship between PA and functional disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Furthermore, LS diagnosed using the GLFS-25 was associated with a lower maximum stride, slower usual gait speed, and longer timed up-and-go time; thus, the GLFS-25 is useful for assessing clinical mobility function. 17 Japanese population-based cohort studies of elderly individuals demonstrated that increased M-PA and V-PA, and decreased sedentary time measured using self-reported questionnaires were associated with a lower risk of functional disability requiring nursing care. 40 Therefore, our findings regarding the relationship between sedentary behavior and LS, defined by the GLFS-25, align with prior research exploring the relationship between PA and functional disability.…”
Section: Discussionmentioning
confidence: 99%
“… 16 The GLFS-25 is a clinically useful tool for assessing mobility in patients with LS. 17 LS was defined as a total GLFS-25 score ≥7, and LS stage was classified based on JOA criteria 18 as follows: LS stage 1: 7-15; LS stage 2: 16-23; and LS stage 3: ≥24. These stages represent the onset of mobility decline, its progression, and a significant decline disrupting social participation, respectively.…”
Section: Methodsmentioning
confidence: 99%